2020
DOI: 10.1039/c9ra08115a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanomagnetic sulphonated impregnated Ni/Mn/Na2SiO3 as catalyst for esterification of palm fatty acid distillate

Abstract: The acidic EFB was doped with magnetic oxides to produce sulphonated nanomagnetic catalysts for biodiesel production from palm fatty acid distillate (PFAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Moreover, they found that a carbonyl group in the test substrates found at certain acid locations could promote the esterification of the lipids, leading to the increase in conversion efficiency to biodiesel, and the as-prepared MOF catalysts could be reused for six reaction cycles. According to the suggested mechanism in Figure a, the carbonyl group of fatty acids is adsorbed on the catalyst to create the protonated carbonyl group at the Lewis acid sites, then alcohol molecules attack the protonated carbonyl group in the state of liquid, and finally the water molecules are eliminated to form biodiesel. , It could be seen that the removal of H 2 O and the fatty acid methyl esters (FAME) molecules restores the active region in the case of MOF, allowing it to take part in the next reaction sequence without becoming poisoned. Under ideal circumstances, ZrSiW/UiO-66 and ZrSiW/Fe-BTC converted oleic acid at 98.0% and 85.5%, correspondingly.…”
Section: Application In Biofuel Productionmentioning
confidence: 99%
“…Moreover, they found that a carbonyl group in the test substrates found at certain acid locations could promote the esterification of the lipids, leading to the increase in conversion efficiency to biodiesel, and the as-prepared MOF catalysts could be reused for six reaction cycles. According to the suggested mechanism in Figure a, the carbonyl group of fatty acids is adsorbed on the catalyst to create the protonated carbonyl group at the Lewis acid sites, then alcohol molecules attack the protonated carbonyl group in the state of liquid, and finally the water molecules are eliminated to form biodiesel. , It could be seen that the removal of H 2 O and the fatty acid methyl esters (FAME) molecules restores the active region in the case of MOF, allowing it to take part in the next reaction sequence without becoming poisoned. Under ideal circumstances, ZrSiW/UiO-66 and ZrSiW/Fe-BTC converted oleic acid at 98.0% and 85.5%, correspondingly.…”
Section: Application In Biofuel Productionmentioning
confidence: 99%
“…The activity of this catalyst is more than half compared to liquid sulfuric acid used. Nehdi and coworkers [40] used empty fruit bunches (EFBs) as a carbon precursor for the synthesis of nano‐magnetic carbonaceous solid acid catalyst. Sulfonation of EFB was carried out to obtain acidic EFBs catalyst which was denoted as AEFBs followed by impregnation of metal oxides NiO, MnO and Na 2 SiO 3 on the catalyst AEFBs.…”
Section: Synthesis Of Biodieselmentioning
confidence: 99%
“…3 (c), the FFA conversion increased up to 96.7% when the reaction temperature was increased from 80 to 120 °C. When temperature increases, reactant molecules gain more kinetic energy which enables them to move faster with more effective collision 27) . As a result, the mass transfer rate accelerated, and higher FAME yield is obtained 5) 28) .…”
Section: Catalytic Esterification Performancesmentioning
confidence: 99%